International encyclopedia of political science - Badie, Bertrand; Berg-Schlosser, Dirk; Morlino, Leonardo (Sage Publications, 2011)
With entries from leading international scholars from around the world, this eight-volume encyclopedia offers the widest possible coverage of key areas both regionally and globally. The International Encyclopedia of Political Science provides a definitive, comprehensive picture of all aspects of political life, recognizing the theoretical and cultural pluralism of our approaches and including findings from the far corners of the world. The eight volumes cover every field of politics, from political theory and methodology to political sociology, comparative politics, public policies, and international relations. Entries are arranged in alphabetical order, and a list of entries by subject area appears in the front of each volume for ease of use. The encyclopedia contains a detailed index as well as extensive bibliographical references. Filling the need for an exhaustive overview of the empirical findings and reflections on politics, this reference resource is suited for undergraduate or graduate students who wish to be informed effectively and quickly on their field of study, for scholars seeking information on relevant research findings in their area of specialization or in related fields, and for lay readers who may lack a formal background in political science but have an interest in the field nonetheless. The International Encyclopedia of Political Science provides an essential, authoritative guide to the state of political science at the start of the 21st century and for decades to come, making it an invaluable resource for a global readership, including researchers, students, citizens, and policy makers. The encyclopedia was developed in partnership with the International Political Science Association. - Publisher